Penggunaan Media Permainan Dadu Untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini - Navisah Meuthia; Suyadi Suyadi (Universitas PGRI Semarang, 2021)
AbstractDuring the golden age, early childhood needs to be given a stimulus according to the stage of early childhood development, where at this stage the child experiences strong abilities in all aspects of development, one aspect of cognitive abilities. This study aims to determine the use of dice game media to improve early childhood cognitive abilities. This research uses descriptive qualitative research. The subjects of this study were children aged 4 to 5 years at TK Alif Surabaya. While the object of this research is the dice game media to improve children's cognitive abilities. The data collection techniques of this research are observation, interview, and documentation. By implementing the steps: 1) Preparing media and material to be conveyed to students. 2) The educator asks the child to sit in a circle, then the educator shows the dice game media, explains the material, explains the rules of play, how to play, where each child will roll the dice, then mentions the picture or number printed on the dice. 3) Evaluation, based on the results of observations made at TK Alif Surabaya, at the end of the learning activity, educators conduct an evaluation to review the learning that has been implemented.Keywords: Cognitive abilities, Dice game AbstrakPada masa golden age, anak usia dini perlu diberikan stimulus yang disesuaikan dengan berkembangnya potensi anak. Pada tahap perkembangan anak, kemampuan kognitifnya sangat baik. Dengan sebab itu, peneltian ini dilakukan melalui permainan dadu demi meningkatkan aspek kognitif anak usia dini. Penelitian ini besifat peneltian kualitatif deskriptif. Subjek dari penelitian yaitu anak TK Alif Surabaya yang berumur 4 sampai 5 tahun. Sedangkan ubtuk objek ialah media permainan dadu untuk meningkatkan kemampuan kognitif anak. Informasi datanya dikumpulkan melalui observasi, wawancara serta dokumentasi. Langkah-langkah yang diterapkan: 1) Menyiapkan media serta materi yang akan diajarkan ke siswa. 2) Anak diminta duduk melingkar, lalu media permainan dadu di tunjukkan pendidik untuk digunakan pada pembelajaran, materi dijelaskan, menjelaskan aturan bermain, cara bermain yaitu setiap anak akan melempar dadu, kemudian menyebutkan gambar atau angka yang tertera pada dadu. 3) Evaluasi, terkait dengan hasil observasi di TK Alif Surabaya, pada akhir kegiatan pembelajaran bertujuan mengkaji kembali pelakasanaan proses pembelajaran.Kata kunci: Kemampuan kognitif, Permainan dadu.